The association of early childhood cognitive development and behavioural difficulties with pre-adolescent problematic eating attitudes. - Rebecca C Richmond; Oleg Skugarevsky; Seungmi Yang; Michael S Kramer; Kaitlin H Wade; Rita Patel; Natalia Bogdanovich; Konstantin Vilchuck; Natalia Sergeichick; George Davey Smith; Emily Oken; Richard M Martin (PLoS ONE)
Objectives Few studies have prospectively investigated associations of child cognitive ability and behavioural difficulties with later eating attitudes. We investigated associations of intelligence quotient (IQ), academic performance and behavioural difficulties at 6.5 years with eating attitudes five years later. Methods We conducted an observational cohort study nested within the Promotion of Breastfeeding Intervention Trial, Belarus. Of 17,046 infants enrolled at birth, 13,751 (80.7%) completed the Children's Eating Attitude Test (ChEAT) at 11.5 years, most with information on IQ (n = 12,667), academic performance (n = 9,954) and behavioural difficulties (n = 11,098) at 6.5 years. The main outcome was a ChEAT score ≥ 85th percentile, indicative of problematic eating attitudes. Results Boys with higher IQ at 6.5 years reported fewer problematic eating attitudes, as assessed by ChEAT scores ≥ 85th percentile, at 11.5 years (OR per SD increase in full-scale IQ = 0.87; 0.79, 0.94). No such association was observed in girls (1.01; 0.93, 1.10) (p for sex-interaction = 0.016). In both boys and girls, teacher-assessed academic performance in non-verbal subjects was inversely associated with high ChEAT scores five years later (OR per unit increase in mathematics ability = 0.88; 0.82, 0.94; and OR per unit increase in ability for other non-verbal subjects = 0.86; 0.79, 0.94). Behavioural difficulties were positively associated with high ChEAT scores five years later (OR per SD increase in teacher-assessed rating = 1.13; 1.07, 1.19). Conclusion Lower IQ, worse non-verbal academic performance and behavioural problems at early school age are positively associated with risk of problematic eating attitudes in early adolescence.